EDUCATION WITH LIMITED FACILITIES AND INFRASTRUCTURE AT SDN PLAJAN - Suparno, Akhmad Diyan; Aliriad, Hilmy; Da'i, Mohammad (Holistic Journal of Sport Education, 2026)
This qualitative research aims to describe teacher's efforts in enhancing student learning interest in Physical Education, Sports, and Health (PJOK) subject with limited facilities and infrastructure at SDN Plajan. The research subjects consisted of 12 fourth-grade students and one PJOK teacher. Data were collected through observation, interviews, and documentation. Data analysis employed qualitative descriptive analysis techniques including data reduction, data presentation, and conclusion drawing. The research findings indicate that the teacher implemented various strategies to overcome facility limitations, including: (1) utilizing alternative spaces such as schoolyards and corridors for learning activities; (2) creating simple teaching aids from locally available materials; (3) implementing rotation systems for equipment usage; (4) modifying games to suit available resources; (5) integrating local wisdom-based traditional games; and (6) collaborating with the school committee and community for facility support. These efforts successfully increased student learning interest from 58% to 85%, as evidenced by increased participation, enthusiasm, and active involvement in learning activities. The research concludes that teacher creativity and innovation play a crucial role in overcoming facility limitations and enhancing student learning interest in PJOK.